The age of AI and our human future - Kissinger, Henry (New York Little Brown and Company, 2021)
Artificial Intelligence (AI) is transforming human society in fundamental and profound ways. Not since the Age of Reason have we changed how we approach security, economics, order, and even knowledge itself. In the Age of AI, three deep and accomplished thinkers come together to consider what AI will mean for us all"
Includes bibliographical references (pages 231-239) and index.
Keywords: Artificial intelligence